Perspectives of Individuals with Multiple Disabilities : A Literature Review - Citra Dwi Azizah; Saskia Nur Maulidya; Vania Nabilah; Raden Roro Tiara Maharany Putri; Lyra Ramania; Citra Ashri Maulidina (GRAB KIDS: Journal of Special Education Need, 2026)
Individuals with multiple disabilities are individuals who have more than one type of disability, present in human diversity. This condition requires extensive and ongoing support and services. Attention to the perspectives of individuals with multiple disabilities in understanding themselves and their surroundings remains limited, particularly in terms of education and social services. In fact, these perspectives are crucial in determining a person's learning experiences, communication styles, level of social engagement, and quality of life. This study aims to analyze in-depth the perspectives of individuals with multiple disabilities and examine the role of the environment in shaping their self-perceptions and life experiences. This study used a descriptive qualitative approach by reviewing relevant scientific articles published in the last five years (2020–2025). Data were analyzed using thematic analysis techniques to identify key patterns in self-perception, learning experiences, communication, and forms of support and barriers originating from family, school, and service systems. The perspectives of individuals with multiple disabilities are formed through the ongoing interaction between personal experiences and environmental responses. Emotional support, responsive communication, and flexible education contribute to the formation of positive self-perceptions, while inadequate services can hinder development and participation. Therefore, the perspectives of individuals with multiple disabilities need to be understood as dynamic social constructs that require an inclusive and adaptive approach to improving quality of life.